A hemalog D analysis of chronic lymphocytic leukaemia and other lymphoproliferative disorders affecting the blood. Issue 5 (May 1981) - Patterson, K G; Goldstone, A H; Richards, J D; Cawley, J C
Abstract : A correlative clinical and Hemalog D study of 80 cases of chronic lymphocytic leukaemia (CLL) was performed and the results compared with those in other lymphoproliferative disorders affecting the blood (eight cases of hairy-cell leukaemia, HCL; three cases of prolymphocytic leukaemia, PLL: two cases of lymphoplasmacytoid proliferation, LPP; and one case of Sézary's syndrome, SS). In CLL the mean percentage and absolute counts of large unstained cells (LUC) were 8.7% and 6.2 x 109/1 (6200/mm3), and the percentage of LUCs was not substantially affected by treatment; there was no correlation between LUCs and Rai clinical stage. SS and LPP were characterised by a similar percentage of LUCs, but both HCL and PLL were distinguished by a higher mean percentage of LUCs. Stage IV CLL was associated with monocytopenia, but other stages of CLL, PLL, LPP, and SS showed no consistent reduction of absolute numbers of non-lymphoid cell types. In contrast, HCL was characterised by a consistent absolute neutropenia and monocytopenia which distinguished its Hemalog D profile from that of PLL.